South Asia Nutrition Knowledge Initiative: Abstract digest March 2025 - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
In this fifth edition of the South Asia Nutrition Knowledge Initiative’s Abstract Digest, we present a diverse body of global, regional, and country-level evidence that, collectively, enhances our understanding of the multifaceted nature of malnutrition, spanning a broad spectrum of outcomes, determinants, and policy responses.